Review of the family Anthogonidae (Diplopoda, Chordeumatida), with descriptions of three new species from the Balkan Peninsula - Antić, Dragan; Dražina, Tvrtko; Raða, Tonći; Tomić, Vladimir T.; Makarov, Slobodan E. (Zootaxa, 2015)
Three new species of the family Anthogonidae are described from caves in Croatia and Montenegro, respectively: Egonpretneria vudutschajldi Antić & Dražina sp. n., Haasia jalzici Antić & Dražina sp. n., and Macrochaetosoma bertiscea Antić & Makarov sp. n. All three subfamilies within Anthogonidae are diagnosed, with brief discussion of relationships between genera and notes on their biogeography. A map of the global distribution of Anthogonidae is presented, as well as maps of the distribution of each species of Balkan anthogonids, including numerous new locality data. The first SEM images are provided for some representatives of this family. A key is given to all seven anthogonid genera. The subfamily Haasiinae Hoffman, 1980 is a new synonym of Anthogonidae, syn. n., while Macrochaetosoma bifurcatum Ćurčić & Makarov, 2001 becomes a new synonym for M. troglomontanum Absolon & Lang, 1933, syn. n..